250 Genome wide Association analyses for meat quality traits in multibreed and crossbred beef cattle. (7th December 2018) - Abo-Ismail, M; Crowley, J; Akanno, E; Li, C; Stothard, P; Aalhus, J; Plastow, G; Basarab, J
Abstract: The objective of this study was to identify the genomic regions associated with Warner-Bratzler shear force (WBSF) and sensory traits at 3 and 29 d ageing via genome wide association study. A total of 982 animals including 486 steers and 495 heifers with proportions of the main breeds including Angus (37%), Charolais (18 %) Hereford (10%), Limousin (11%) and Simental (8%) had actual and imputed high density genotypes (HD; n=414, 469 SNPs). The association analyses were performed using linear mixed models implemented in GCTA software. The genomic heritability for tenderness and meat quality traits using the HD SNP were estimated using GVCBLUP software and ranged from 0.01 to 0.32 for sustained juiciness and WBSF at 3 d of aging, respectively. A total of 518 SNPs showed association (P < 0.00009) located with, or nearby (at ±100k base) 835 genes. Some of the detected associations were previously reported including CAPN1 which was found to be associated with tenderness at 29 din this dataset. The olfactory transduction pathway was the most significantly (P < 0.001) enriched pathway using the Database for Annotation, Visualization and Integrated Discovery (DAVID v6.8). In addition, the DAVID analyses suggested 36 and 23 genes involved in sensory perception of chemical stimulus (at 0.06 % false discovery rate; FDR) and sensory perception of smell, respectively, as the most significant (6% FDR) enriched mechanisms contributing to the genetic variation of meat quality and sensory traits in the current study. With availability of whole genome sequence genotypes, the associated genomic regions found in the current study will be investigated further in order to search for causal variants for meat tenderness and quality traits in the beef cattle.